Clinical and treatment patterns in neuromyelitis optica: a retrospective study from a single centre - Jagiasi, Kamlesh A.; Nagendra, Shashank; Ansari, Afroz; Barvalia, Prachi; Aglave, Vikram (International Journal of Advances in Medicine, 2019)
Background: The aim of the study was to study the different presentations, treatment patterns and relapses on therapy in patients of neuromyelitis optica (NMO) and neuromyelitis optica spectrum disorder (NMOSD). Methods: This is a retrospective, observational study in a tertiary hospital where Demographics, clinical manifestations at onset and at follow up and relapses, serum anti Aquaporin 4 antibody status, first line immunomodulatory therapy which was initiated and Relapses on first line therapy were noted. Results: Demographics and clinical presentation was largely similar to published data. 80% patients presented with LETM/ON at onset. Ten patients relapsed on oral therapy and trend was to shift from oral therapy to RTX after relapse on oral agent. No relapses were noted on RTX. Conclusions: Unaffordability and apprehension towards injections and cost were the factors affecting IMT decision, so majority received oral agents Aza/ MMF as first line therapy while remaining patients on oral therapy remained relapse free.